Structural Effect of Palladium on Carbon Catalyst for Hexafluoropropylene Hydrogenation - Kim, Chang Soo; Yoo, Kye Sang (American Scientific Publishers, 2015)
Palladium was impregnated on carbon particles with various structures using 1-hexyl-3-methylimidazolium hexafluorophosphate ([Hmim][PF6]) to synthesize a catalyst for hexafluoropropylene hydrogenation. Under the identical reaction conditions (1 bar and 120 degrees C), the catalyst with mesoporosity (pore size > 500 nm) showed higher than 80% reactant conversion. However, the conversion over the catalyst possessed small pore size was very low. Moreover, the catalyst prepared with ionic liquids was more stable than without ionic liquids.